The Language of Resistance in Wiji Thukul's Nyanyian Akar Rumput: A Critical Discourse Analysis - Apriliana, Milda (Polyglot: Journal of Linguistics, Literature, and Language Education, 2025)
This study aims to uncover the language strategies of resistance used by Wiji Thukul in his poem Nyanyian Akar Rumput through a critical discourse analysis approach. Data obtained from the poem's text as the primary source are analyzed using Fairclough's critical discourse analysis framework, which encompasses aspects of text, discourse practice, and social practice. The results of the study indicate that the symbol "grassroots" represents the common people who possess collective resilience and strength in facing it. Metaphors are used to construct an image of injustice while simultaneously sowing a spirit of resistance, while calls and appeals function to form a collective awareness. The choice of simple yet meaningful diction strengthens the emotional connection between the poet and his readers. These findings emphasize that language in Nyanyian Akar Rumput serves not only as a means of aesthetic expression but also as a political instrument to articulate a counter-discourse against the dominance of power and drive social change.